Waste bank data processing system in palembang city - Zulhipni Reno Saputra Elsi; Ayundha Lathary (International Journal Cister, 2023)
The development of web technology is getting better with the support of an adequate internet connection in the environment. Waste Bank is a term for waste management activities where the community (referred to as customers) deposit waste where the deposited waste is still suitable for sale or recycling such as plastic, paper, iron, battery, aluminum and others to the Waste Bank manager. as an effort to maximize the value of waste with the aim of creating a healthy, clean, green and beautiful environment, reducing waste to landfill, changing people's behavior, educating people about environmental care and organization, increasing creativity, and providing benefits for waste producers. The research methodology used in making this web-based information system is the Waterfall methodology which includes system engineering, analysis, design , coding and testing. The research design method uses descriptive methods, while the data collection methods use observation and interview methods. There is also software for program design and implementation using Xampp as a server . The results of the research can be used by officers for inputting registration and transactions carried out, and leaders can find out information on monthly transaction reports and customers can find out details of transactions that have been carried out through the web.